2016
DOI: 10.1080/15732479.2016.1173071
|View full text |Cite
|
Sign up to set email alerts
|

A spatial multicriteria decision-making method for natural gas transmission pipeline routing

Abstract: In accordance with current demands, the natural gas transmission pipeline (NGTP) is one of the most appropriate methods used in the distribution of existing reserves. Construction of long-distance pipelines requires large expenditures. Decreasing the time and cost of such construction and minimising environmental damage depend upon identifying the optimum routes from the onset of the project. Route determination is one of the most important steps in NGTP projects. The route determination process requires obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…The GIS has the capability to combine thematic data layers to create a cost surface from which the optimal forest road route is calculated. The S-MCDM method integrates GIS technologies with complex decisionmaking in a way that provides a successful outcome (Yıldırım et al 2016b). This study demonstrated the increased effectiveness of integrating GIS technologies with S-TOPSIS, especially in forest road route.…”
Section: Rezultati I Raspravamentioning
confidence: 87%
“…The GIS has the capability to combine thematic data layers to create a cost surface from which the optimal forest road route is calculated. The S-MCDM method integrates GIS technologies with complex decisionmaking in a way that provides a successful outcome (Yıldırım et al 2016b). This study demonstrated the increased effectiveness of integrating GIS technologies with S-TOPSIS, especially in forest road route.…”
Section: Rezultati I Raspravamentioning
confidence: 87%
“…In raster-based approaches, each criterion can be expressed as a map that involves the decision alternatives (locations), whereas, for vector-based approaches, attribute fields and columns are used to represent the set of criteria for geographical features. There is a variety of different application domains that addresses S-MCDM, such as landscape assessment, environmental protection, utility management, sustainable and regional development, water resource management, land use planning, site planning, natural hazard risk assessment, waste management and network infrastructure planning [74][75][76][77][78][79][80][81][82][83][84]. Those application domains incorporate various mathematical models such as weighted linear combination [17], ordered weighted averaging [85][86][87], ideal point [60,88] or analytic hierarchy process [19] to compute the performance of the alternatives (e.g., cities or districts of a city).…”
Section: Discussionmentioning
confidence: 99%
“…Busca-se o consenso do julgamento do grupo de especialistas, a im de analisar a in luencia da ponderação dos diferentes criteŕios sob a escolha do veıćulo de carga mais ecoe iciente entre as alternativas avaliadas. Já a metodologia TOPSIS representa a lógica do raciocıńio da escolha humana, determina um valor escalar que responde simultaneamente as melhores e piores alternativas (Yildirim et al, 2016) sendo utilizada para ranquear as alternativas (Karahalios, 2017).…”
Section: Proposição De Modelo Híbrido Ahp-topsisunclassified